Employment of Land-Expropriated Farmers: The Effects of Land Expropriation and Gender Difference - Yue Wang; Dengjiao Liao; Bin Yan; Xinhai Lu (Land, 2023)
The employment inequality between males and females in the context of land expropriation is not conducive for land-expropriated farmers to earn a sustainable livelihood. In this study, based on the data of two waves of household surveys, the “Chinese Family Panel Study” in 2016 and 2018, the PSM-DID method is used to test the effects of land expropriation on the employment behavior of the rural labor force, and the heterogeneous results of men’s and women’s employment behaviors are analyzed. The following conclusions are drawn. Land expropriation significantly reduces the employment probability of the labor force, encouraging the rural labor force to withdraw from the labor market voluntarily; land expropriation significantly shortens the employment distance of the labor force overall, promoting the urbanization of the rural labor force in the vicinity; land expropriation has a greater impact on the unemployment of the female labor force than that of the male labor force, and it increases the employment distance of males and reduces that of females, promoting the return of females’ labor to the family. The policy significance of this study is to attach importance to the long-term sustainable livelihoods of rural households and the employment equality of males and females in urbanization. Findings suggest family–friendly compensation for land expropriation should be formulated, rural construction land should be allowed to enter the market instead of being expropriated, and cooperation between county and developed regions should be encouraged for the creation of more jobs.